Multiplexing detection of IgG against Plasmodium falciparum pregnancy-specific antigens - Fonseca, Ana Maria (PLoS One, 2017)
BACKGROUND: Pregnant women exposed to Plasmodium falciparum generate antibodies against VAR2CSA, the parasite protein that mediates adhesion of infected erythrocytes to the placenta. There is a need of high-throughput tools to determine the fine specificity of these antibodies that can be used to identify immune correlates of protection and exposure. Here we aimed at developing a multiplex-immunoassay to detect antibodies against VAR2CSA antigens. METHODS AND FINDINGS: We constructed two multiplex-bead arrays, one composed of 3 VAR2CSA recombinant-domains (DBL3X, DBL5Ɛ and DBL6Ɛ) and another composed of 46 new peptides covering VAR2CSA conserved and semi-conserved regions. IgG reactivity was similar in multiplexed and singleplexed determinations (Pearson correlation, protein array: R(2) = 0.99 and peptide array: R(2) = 0.87). IgG recognition of 25 out of 46 peptides and all recombinant-domains was higher in pregnant Mozambican women (n = 106) than in Mozambican men (n = 102) and Spanish individuals (n = 101; p<0.05). Agreement of IgG levels detected in cryopreserved plasma and in elutions from dried blood spots was good after exclusion of inappropriate filter papers. Under heterogeneous levels of exposure to malaria, similar seropositivity cutoffs were obtained using finite mixture models applied to antibodies measured on pregnant Mozambican women and average of antibodies measured on pregnant Spanish women never exposed to malaria. The application of the multiplex-bead array developed here, allowed the assessment of higher IgG levels and seroprevalences against VAR2CSA-derived antigens in women pregnant during 2003–2005 than during 2010–2012, in accordance with the levels of malaria transmission reported for these years in Mozambique. CONCLUSIONS: The multiplex bead-based immunoassay to detect antibodies against selected 25 VAR2CSA new-peptides and recombinant-domains was successfully implemented. Analysis of field samples showed that responses were specific among pregnant women and dependent on the level of exposure to malaria. This platform provides a high-throughput approach to investigating correlates of protection and identifying serological markers of exposure for malaria in pregnancy.